1990
DOI: 10.1007/bf01313241
|View full text |Cite
|
Sign up to set email alerts
|

Variability of nitrate concentration in nitrogen-depleted subtropical surface waters

Abstract: Recent improvements in the analytical determination of nitrate and nitrite allow measurements of nanomolar concentrations in nitrogen-depleted surface waters, revealing variability not previously observable. The new methods allow direct observation of net nitrate consumption and production measured as changes in nitrate concentration over time in incubated samples of seawater. We find that nitrate concentrations in nitrogendepleted surface waters show regional differences, and sometimes diel differences. The v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…NO,-concentration was determined at the beginning and end of the incubations as before. In situ changes in N03-concentration were <20 nM between morning and evening samples from the upper 20 m, indicating NO,-consumption during the day that agreed well with the incubation results (Eppley et al 1990). Sixteen daytime and four overnight experiments yielded successful depth profiles of net changes in N03-concentration.…”
Section: Acknowledgmentssupporting
confidence: 74%
See 3 more Smart Citations
“…NO,-concentration was determined at the beginning and end of the incubations as before. In situ changes in N03-concentration were <20 nM between morning and evening samples from the upper 20 m, indicating NO,-consumption during the day that agreed well with the incubation results (Eppley et al 1990). Sixteen daytime and four overnight experiments yielded successful depth profiles of net changes in N03-concentration.…”
Section: Acknowledgmentssupporting
confidence: 74%
“…4). Other examples of apparent nitrification during this cruise were reported earlier (Eppley et al 1990). …”
Section: Acknowledgmentsmentioning
confidence: 93%
See 2 more Smart Citations
“…Since the development of sensitive analytical procedures, it has been shown that nitrate concentrations of subtropical surface waters over much of the world's oceans, including the subtropical gyres, is often at sub-micromolar concentrations (3 to <50 nmoles l −1 ). Using a chemiluminescent method, Garside (1985) and Eppley et al (1990) previously found nitrate concentrations <10 nM in the Sargasso Sea and in the subtropical Pacific. These concentrations, which would be depleted in a few hours by the ambient assemblages of phytoplankton, were low but not zero.…”
Section: Discussionmentioning
confidence: 99%